Coronary Circulation and Hemodynamics - Hendry Purnasidha Bagaswoto; Erika Maharani; Budi Yuli Setianto (ACI (Acta Cardiologia Indonesiana), 2016)
Coronary circulation is the circulation of blood in the blood vessels of the heart muscle (myocardium). The vessels that deliver oxygenrich blood to the myocardium are known as coronary arteries. The vessels that remove thedeoxygenated blood from the heart muscle are known as cardiac veins.